2004
DOI: 10.1063/1.1768172
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution kinetic energy release distributions and dissociation energies for fullerene ions Cn+, 42⩽n⩽90

Abstract: We have measured the kinetic energy released in the unimolecular dissociation of fullerene ions, Cn+ --> C(n-2)+ + C2, for sizes 42 < or = n < or = 90. A three-sector-field mass spectrometer equipped with two electric sectors has been used in order to ensure that contributions from isotopomers of different masses do not distort the experimental kinetic energy release distributions. We apply the concept of microcanonical temperature to derive from these data the dissociation energies of fullerene cations. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 83 publications
4
50
0
Order By: Relevance
“…Above C 86 , the E n -values increase with n. As an example E 128 = 16.5Ϯ 0.8 meV, which allows for about seven E KER = 150 meV C 2 -emissions. 30,31 We have already concluded that the new larger C n + fullerenes only are formed with sufficiently large ͓C 60 ͔ m clusters in the target and it appears that both the magic fullerenes and the hot giant fullerenes are formed in ͓C 60 ͔ m bulks. There, C 60 molecules near central trajectories ͑cf.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Above C 86 , the E n -values increase with n. As an example E 128 = 16.5Ϯ 0.8 meV, which allows for about seven E KER = 150 meV C 2 -emissions. 30,31 We have already concluded that the new larger C n + fullerenes only are formed with sufficiently large ͓C 60 ͔ m clusters in the target and it appears that both the magic fullerenes and the hot giant fullerenes are formed in ͓C 60 ͔ m bulks. There, C 60 molecules near central trajectories ͑cf.…”
Section: Resultsmentioning
confidence: 99%
“…The measured E n -values for C 70 -C 86 are only 4-5 meV and thus far too small for any charge separation process ͑as, e.g., C 2 + -emission͒ or for longer sequences of neutral C 2 emissions. 30,31 Instead, it appears that these fullerenes form through size-up processes and fragmentation in few steps only. Above C 86 , the E n -values increase with n. As an example E 128 = 16.5Ϯ 0.8 meV, which allows for about seven E KER = 150 meV C 2 -emissions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For fullerenes in the C 40 to C 90 size range, the dissociation energy for C 2 loss is usually assumed to be between 8 and 11 eV. 28 The observation of fragments as small as C 32 + therefore implies that on the order of 14ϫ 9 eV= 126 eV of additional energy have to be deposited via IR absorption into the system! Even if most of the fragmentation below C 40 + is dominated by a cleavage mechanism ͑leading to C m 0 , m =4,6,... emission͒, 2 this rough estimation still holds.…”
Section: Resultsmentioning
confidence: 99%
“…In condensed matter physics, clusters dissociation induced by photo-ionization [1,2,3,4] or charge transfer collisions [5,6], cannot be studied without properly accounting for the time window of the experiment [1]. Going down to the femto-scale, the thermodynamic properties of nuclear systems can only be accessed through collisions [9].…”
Section: Introductionmentioning
confidence: 99%